Stress Fracture Risk Factors in Basic Combat Training - Knapik, J.; Montain, S. J.; McGraw, S.; Grier, T.; Ely, M.; Jones, B. H. (International Journal of Sports Medicine, 2012)
This study examined demographic and physical risk factors for stress fractures in a large cohort of basic trainees. New recruits participating in US Army BCT from 1997 through 2007 were identified, and birth year, race/ethnicity, physical characteristics, body mass index, and injuries were obtained from electronic databases. Injury cases were recruits medically diagnosed with inpatient or outpatient stress fractures. There were 475 745 men and 107 906 women. Stress fractures incidences were 19.3 and 79.9 cases/1 000 recruits for men and women, respectively. Factors that increased stress fracture risk for both men and women included older age, lower body weight, lower BMI, and race/ethnicity other than black. Compared to Asians, those of white race/ethnicity were at higher stress fractures risk. In addition, men, but not women, who were taller or heavier were at increased stress fracture risk. Stress fracture risk generally increased with age (17–35 year range) at a rate of 2.2 and 3.9 cases/1 000 recruits per year for men and women, respectively. This was the largest sample of military recruits ever examined for stress fractures and found that stress fracture risk was elevated among recruits who were female, older, had lower body weight, had lower BMI, and/or were not of black race/ethnicity.
Keywords: age; gender; body mass index; height; weight; race/ethnicity